Welfare Analysis of Fiscal Reforms: Does the Representation of the Family Decision Process Matter? Evidence for Germany - François Laisney; Denis Beninger; Miriam Beblo (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
This paper compares predictions obtained for the analysis of tax reforms with collective and unitary models of household labour supply and consumption behaviour. We simulate real world microdata by means of a collective approach, using a compound procedure of estimation and calibration based on the 1998 wave of the German socioeconomic panel. We estimate a unitary model on this ?collective? data set. Investigating a move from joint to individual taxation on the basis of both models, we obtain important discrepancies between predicted adjustments to labour supply and distortions in the welfare analysis of the reform on the basis of unitary estimates. These results suggest that increased efforts should be devoted to the estimation of collective models with taxation.
Keywords: D12; J22; D11; 330; Collective model; household labour supply; intra household allocations; Steuerreform; Familienökonomik; Haushaltsökonomik; Arbeitsangebot; Gesamtwirtschaftlicher Konsum; Schätzung; Deutschland